Forecasting Produksi Perikanan Budidaya Di Kota Palembang Dengan Metode Autoregressive Integrated Moving Average (ARIMA) - Rahma Mulyani; Yulia Puspita Sari; Sumantriyadi Sumantriyadi (Universitas PGRI Palembang, 2022)
The number of aquaculture households in Palembang City continues to increase from 2017 only 682 households to 1,050 households in 2018. But on the contrary in terms of the amount of aquaculture production, the total production decreased by 24,259 tons in 2014 and only 20,327 tons in 2017 (BPS, 2018). One of the steps that can be taken to determine the condition of aquaculture in Palembang is by doing forecasting. This is useful for knowing or predicting the results of aquaculture production with precise accuracy. This study aims to determine the prediction of aquaculture production in Palembang City using the Autoregressive Integrated Moving Average (ARIMA) method. The results of the ACF and PACF plots show that both plots have a tail off pattern. the predictive model obtained is ARIMA (1,0,1) but after over fitting the model, the ARIMA model (2,0,1) is the best model because it has the smallest MAPE value, which is 48,30. Based on the ARIMA model (2,0.1), the forecast values for aquaculture production in Palembang City from 2021 to 2030 are 19542,598 tons, 12846,331 tons, 50682,093 tons, 43389,831 tons, 15352,492 tons. , 9595,313 tons, 26140,949 tons, 36258,543 tons, 29041,898 tons, and 19548.050 tons